Big data systems : a 360-degree approach - Shamsi, Jawwad Ahmad; Khojaye, Muhammad AlI (Boca Raton : Chapman & Hall/CRC, 2021)
Big Data Systems encompass massive challenges related to data diversity, storage mechanisms, and requirements of massive computational power. Further, capabilities of big data systems also vary with respect to type of problems. For instance, distributed memory systems are not recommended for iterative algorithms. Similarly, variations in big data systems also exist related to consistency and fault tolerance. The purpose of this book is to provide a detailed explanation of big data systems. The book covers various topics including Networking, Security, Privacy, Storage, Computation, Cloud Computing, NoSQL and NewSQL systems, High Performance Computing, and Deep Learning. An illustrative and practical approach has been adopted in which theoretical topics have been aided by well-explained programming and illustrative examples. Key Features: Introduces concepts and evolution of Big Data technology. Illustrates examples for thorough understanding. Contains programming examples for hands on development. Explains a variety of topics including NoSQL Systems, NewSQL systems, Security, Privacy, Networking, Cloud, High Performance Computing, and Deep Learning. Exemplifies widely used big data technologies such as Hadoop and Spark. Includes discussion on case studies and open issues. Provides end of chapter questions for enhanced learning.
Preface Author Bios Acknowledgements List of Figures List of Tables Introduction to Big Data Systems 1.1 INTRODUCTION: REVIEW OF BIG DATA SYSTEMS 1.2 UNDERSTANDING BIG DATA 1.3 TYPE OF DATA: TRANSACTIONAL OR ANALYTICAL 1.4 REQUIREMENTS AND CHALLENGES OF BIG DATA 1.5 CONCLUDING REMARKS 1.6 FURTHER READING 1.7 EXERCISE QUESTIONS Architecture and Organization of Big Data Systems 2.1 ARCHITECTURE FOR BIG DATA SYSTEMS 2.2 ORGANIZATION OF BIG DATA SYSTEMS: CLUSTERS 2.3 CLASSIFICATION OF CLUSTERS: DISTRIBUTED MEMORY VS. SHARED MEMORY 2.4 CONCLUDING REMARKS 2.5 FURTHER READING 2.6 EXERCISE QUESTIONS Cloud Computing for Big Data 3.1 CLOUD COMPUTING 3.2 VIRTUALIZATION 3.3 PROCESSOR VIRTUALIZATION 3.4 CONTAINERIZATION 3.5 VIRTUALIZATION OR CONTAINERIZATION 3.6 FOG COMPUTING 3.7 EXAMPLES 3.8 CONCLUDING REMARKS 3.9 FURTHER READING 3.10 EXERCISE QUESTIONS HADOOP: An Efficient Platform for Storing and Processing Big Data 4.1 REQUIREMENTS FOR PROCESSING AND STORING BIG DATA 4.2 HADOOP -- THE BIG PICTURE 4.3 HADOOP DISTRIBUTED FILE SYSTEM 4.4 MAPREDUCE 4.5 HBASE 4.6 CONCLUDING REMARKS 4.7 FURTHER READING 4.8 EXERCISE QUESTIONS Enhancements in Hadoop 5.1 ISSUES WITH HADOOP 5.2 YARN 5.3 PIG 5.4 HIVE 5.5 DREMEL 5.6 IMPALA 5.7 DRILL 5.8 DATA TRANSFER 5.9 AMBARI 5.10 CONCLUDING REMARKS 5.11 FURTHER READING 5.12 EXERCISE QUESTIONS Spark 6.1 LIMITATIONS OF MAPREDUCE 6.2 INTRODUCTION TO SPARK 6.3 SPARK CONCEPTS 6.4 SPARK SQL 6.5 SPARK MLLIB 6.6 STREAM BASED SYSTEM 6.7 SPARK STREAMING 6.8 CONCLUDING REMARKS 6.9 FURTHER READING 6.10 EXERCISE QUESTIONS NoSQL Systems 7.1 INTRODUCTION 7.2 HANDLING BIG DATA SYSTEMS -- PARALLEL RDBMS 7.3 EMERGENCE OF NOSQL SYSTEMS 7.4 KEY-VALUE DATABASE 7.5 DOCUMENT-ORIENTED DATABASE 7.6 COLUMN-ORIENTED DATABASE 7.7 GRAPH DATABASE 7.8 CONCLUDING REMARKS 7.9 FURTHER READING 7.10 EXERCISE QUESTIONS NewSQL Systems 8.1 INTRODUCTION 8.2 TYPES OF NEWSQL SYSTEMS 8.3 FEATURES 8.4 NEWSQL SYSTEMS: CASE STUDIES 8.5 CONCLUDING REMARKS 8.6 FURTHER READING 8.7 EXERCISE QUESTIONS Networking for Big Data 9.1 NETWORK ARCHITECTURE FOR BIG DATA SYSTEMS 9.2 CHALLENGES AND REQUIREMENTS 9.3 NETWORK PROGRAMMABILITY AND SOFTWARE DEFINED NETWORKING 9.4 LOW LATENCY AND HIGH SPEED DATA TRANSFER 9.5 AVOIDING TCP INCAST -- ACHIEVING LOW LATENCY AND HIGH THROUGHPUT 9.6 FAULT TOLERANCE 9.7 CONCLUDING REMARKS 9.8 FURTHER READING 9.9 EXERCISE QUESTIONS Security for Big Data 10.1 INTRODUCTION 10.2 SECURITY REQUIREMENTS 10.3 SECURITY: ATTACK TYPES AND MECHANISMS 10.4 ATTACK DETECTION AND PREVENTION 10.5 CONCLUDING REMARKS 10.6 FURTHER READING 10.7 EXERCISE QUESTIONS Privacy for Big Data 11.1 INTRODUCTION 11.2 UNDERSTANDING BIG DATA AND PRIVACY 11.3 PRIVACY VIOLATIONS AND THEIR IMPACT 11.4 TYPES OF PRIVACY VIOLATIONS 11.5 PRIVACY PROTECTION SOLUTIONS AND THEIR LIMITATIONS 11.6 CONCLUDING REMARKS 11.7 FURTHER READING 11.8 EXERCISE QUESTIONS High Performance Computing for Big Data 12.1 INTRODUCTION 12.2 SCALABILITY: NEED FOR HPC 12.3 GRAPHIC PROCESSING UNIT 12.4 TENSOR PROCESSING UNIT 12.5 HIGH SPEED INTERCONNECTS 12.6 MESSAGE PASSING INTERFACE 12.7 OPENMP 12.8 OTHER FRAMEWORKS 12.9 CONCLUDING REMARKS 12.10 FURTHER READING 12.11 EXERCISE QUESTIONS Deep Learning with Big Data 13.1 INTRODUCTION 13.2 FUNDAMENTALS 13.3 NEURAL NETWORK 13.4 TYPES OF DEEP NEURAL NETWORK 13.5 BIG DATA APPLICATIONS USING DEEP LEARNING 13.6 CONCLUDING REMARKS 13.7 FURTHER READING 13.8 EXERCISE QUESTIONS Big Data Case Studies 14.1 GOOGLE EARTH ENGINE 14.2 FACEBOOK MESSAGES APPLICATION 14.3 HADOOP FOR REAL-TIME ANALYTICS 14.4 BIG DATA PROCESSING AT UBER 14.5 BIG DATA PROCESSING AT LINKEDIN 14.6 DISTRIBUTED GRAPH PROCESSING AT GOOGLE 14.7 FUTURE TRENDS 14.8 CONCLUDING REMARKS 14.9 FURTHER READING 14.10 EXERCISE QUESTIONS Bibliography Index
Previously issued in print: 2020.
OCLC-licensed vendor bibliographic record.
Keywords: Big data; Systems engineering; COMPUTERS / Database Management / Data Mining; BUSINESS & ECONOMICS / Statistics; COMPUTERS / Database Management / General